Emulsifying food microparticles prepared from cocoa by-product - Cuthill, Holly (2020)
This PhD research concerned the preparation of emulsifying food microparticles from a plant-based by-product of the food manufacturing industry, thereby increasing the efficient use of natural resources. In the early stages of this research, and at the time relevant to the product spectrum of the sponsoring industry partner, spent coffee grounds and cocoa shell were evaluated as feedstock. Coconut shell was considered for the higher natural lignin content. Cocoa shell was taken forward from results showing the largest droplet density on the surface of the biomass following hydrothermal pre treatment. The droplets were hypothesised to be lignin rich and therefore this densely covered surface was preferred prior to extraction. The process involved preparing a lignin-rich extract from the feedstock followed by anti solvent precipitation into spherical microparticles sized between 0.05 and 0.8 µm. As lignin is a largely hydrophobic polymer, these microparticles were hypothesised to stabilise emulsions through the Pickering mechanisms. It was further hypothesised that the conditions of the extraction protocol, and the microparticulation process would allow control over particle surface hydrophobicity, thus whether water-in-oil or oil-in-water emulsions would be preferentially stabilised, and particle size, impacting on emulsion droplet size. The rule of thumb is that Pickering stabilisation require particles an order of magnitude smaller in diameter than the desired emulsion droplet size spectrum.